Analisis Penyalahgunaan Keadaan Dalam Pembatalan Akta Hibah Dan Pembagian Harta Bersama (Studi Kasus Putusan No.83/Pdt.G/2022/PN CBN) - Abdullah, Ali; Barus, Zulfadli; Rusmawati, Nurlia (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
This study discusses the abuse of circumstances in the revocation of a gift deed and the division of joint property, focusing on Decision No. 83/Pdt.G/2022/PN Cbn. Abuse of circumstances occurs when one party exploits the weakness or lack of understanding of the other party in agreeing to the gift deed, leading to unfairness in the division of joint property. In this case, the defendant, with the assistance of the Land Deed Official (PPAT), created the gift deed without the plaintiff’s consent, resulting in an unfair division of joint property. The gift deed made without the presence and approval of the plaintiff is considered invalid under Articles 1320 and 1321 of the Indonesian Civil Code due to defects in will caused by abuse of circumstances. This study uses a normative juridical method with a case study approach. The findings show that a gift deed made through abuse of circumstances can be revoked as it violates contract law in Indonesia. Furthermore, the plaintiff has the right to file a lawsuit for the cancellation of the deed and claim compensation for the damages incurred. Legal protection is necessary in the process of dividing joint property to ensure fairness, especially after divorce. This study emphasizes the importance of supervision in the creation of gift deeds and the responsibility of the PPAT to ensure that all parties understand the legal consequences